The complex puzzle of dietary silver nanoparticles, mucus and microbiota in the gut. (17th February 2020) - Bi, Yuqiang; Marcus, Andrew K.; Robert, Hervé; Krajmalnik-Brown, Rosa; Rittmann, Bruce E.; Westerhoff, Paul; Ropers, Marie-Hélène; Mercier-Bonin, Muriel
ABSTRACT: Hundreds of consumer and commercial products containing silver nanoparticles (AgNPs) are currently used in food, personal-care products, pharmaceutical, and many other applications. Human exposure to AgNPs includes oral intake, inhalation, and dermal contact. The aim of this review was to focus on oral intake, intentional and incidental of AgNPs where well-known antimicrobial characteristics that might affect the microbiome and mucus in the gastrointestinal tract (GIT). This critical review summarizes what is known regarding the impacts of AgNPs on gut homeostasis. It is fundamental to understand the forms of AgNPs and their physicochemical characterization before and during digestion. For example, lab-synthesized AgNPs differ from "real" ingestable AgNPs used as food additives and dietary supplements. Similarly, the gut environment alters the chemical and physical state of Ag that is ingested as AgNPs. Emerging research on in vitro and in vivo rodent and human indicated complex multi-directional relationships among AgNPs, the intestinal microbiota, and the epithelial mucus. It may be necessary to go beyond today's descriptive approach to a modeling-based ecosystem approach that might quantitatively integrate spatio-temporal interactions among microbial groups, host factors (e.g., mucus), and environmental factors, including lifestyle-based stressors. It is suggested that future research (1) utilize more representative AgNPs, focus on microbe/mucus interactions, (2) assess the effects of environmental stressors for longer and longitudinal conditions, and (3) be integrated using quantitative modeling.